Construction and analysis of circular RNA-associated competing endogenous RNA network in the hippocampus of aged mice for the occurrence of postoperative cognitive dysfunction - Zhang, Mingzhu; Suo, Zizheng; Qu, Yinyin; Zheng, Yuxiang; Xu, Wenjie; Zhang, Bowen; Wang, Qiang; Wu, Linxin; Li, Shuai; Cheng, Yaozhong; Xiao, Ting; Zheng, Hui; et al. (Frontiers in Aging Neuroscience, 2023)
Circular RNAs are highly stable single-stranded circular RNAs and enriched in the brain. Previous studies showed that circRNAs, as part of competing endogenous RNAs (ceRNAs) network, play an important role in neurodegenerative and psychiatric diseases. However, the mechanism of circRNA-related ceRNA networks in postoperative cognitive dysfunction (POCD) has not been elucidated yet. POCD usually occurs in elderly patients and is characterized by hippocampal dysfunction. Here, aged C57BL/6 mice were subjected to exploratory laparotomy under sevoflurane anesthesia, and this POCD model was verified by Morris water maze test. Whole-transcriptome sequencing was performed on the hippocampus of control group (Con) and surgery group. One hundred and seventy-seven DEcircRNAs, 221 DEmiRNAs and 2,052 DEmRNAs were identified between two groups. A ceRNA network was established with 92 DEcircRNAs having binding sites with 76 DEmiRNAs and 549 target DEmRNAs. In functional enrichment analysis, a pathological pattern of POCD was highlighted in the ceRNA network: Abnormal metabolic process in neural cells, including oxygen metabolism, could promote apoptosis and then affect the synaptic function, which may undermine the neural plasticity and eventually lead to changes in cognitive function and other behavioral patterns. In conclusion, this specific ceRNA network of circRNAs–miRNAs–mRNAs has provided novel insights into the regulatory mechanisms of POCD and revealed potential therapeutic gene targets.